Semi-Netnography Analysis Of Forced Marriage In The Film Hati Suhita: Islamic Family Law Perspective - Aldi Fauzan; Muhammad Taufan Badolahi; Yuni Amelia (UNIVERSITAS PAKUAN, 2026)
Forced marriage is a marriage that is performed due to pressure or coercion from other parties, such as parents, family, or the social environment. This study aims to analyze the cultural phenomenon of forced marriage in the film Hati Suhita based on the perspective of Islamic Family Law. This research focuses on the practice of forced marriage represented in the film Hati Suhita through dialogue, scenes, and storylines. The method used in this study is qualitative-descriptive with a literature study approach and semi-netnography analysis to understand the phenomenon of forced marriage practices. The results of the study show that the marriage between Gus Birru and Alina Suhita is a form of forced arranged marriage due to family pressure and the authority of his father as a kiai. This condition leads to emotional conflict, rejection, and lack of communication, as well as disharmony in their household. From the perspective of Islamic Family Law, the practice of forced marriage in the film Hati-Suhita occurs because of ijbar rights, which are the reason for coercion in marriage, the legitimacy of the family, and the cultural authority of the Islamic boarding school. The preventive solution is to provide premarital guidance to both parties to minimize conflicts in the household. Although the concept of arranged marriage in Islam is allowed, its implementation must be based on the agreement and willingness of both parties so that the goals of marriage such as the creation of a harmonious, just, and peaceful family, can be realized.